Sistem Pendukung Keputusan Penilaian Kinerja Pegawai Non-ASN Menggunakan Metode MOORA pada UPTD Puskesmas Kosambi - Adih Adih; Wahyu Aji Dwi Pangestu; Purnama Sari; Joko Suwarno (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Employee performance represents the ability to fulfill tasks and responsibilities according to organizational standards. At UPTD Puskesmas Kosambi, the evaluation of Non-Civil Servant (Non-ASN) healthcare workers is still done manually and tends to be subjective, primarily based on attendance. This study aims to address the issue by developing a decision support system using the MOORA (Multi-Objective Optimization on the Basis of Ratio Analysis) method. A descriptive-applied approach and the waterfall development model were employed. Five evaluation criteria were used: attendance (25%), service quality (35%), report timeliness (20%), patient complaints (10%), and lateness (10%). Data from 20 Non-ASN healthcare workers in April 2025 were analyzed, with Anis Julianti achieving the highest MOORA score of 0.3839. The system underwent validation through black-box testing and user acceptance testing (UAT), both confirming its accuracy and usability. The findings were compared with previous studies. Harningsih et al. (2024) used the MOORA method for promotion evaluations at the North Sumatra Provincial Inspectorate Office and recorded a top score of 0.3616. Dewi Yohana br Ginting et al. (2024) applied the method at a beauty clinic and found a top score of 0.3747. These comparisons indicate that the MOORA results in this study fall within a consistent and valid range. The developed decision support system is expected to enhance the objectivity, transparency, and accountability of performance evaluations for Non-ASN employees in primary healthcare services, offering a more comprehensive alternative to manual assessment methods.